The importance of the internal information environment for tax avoidance - Gallemore, John; Labro, Eva (Journal of Accounting and Economics, 2015)
We show that firms׳ ability to avoid taxes is affected by the quality of their internal information environment, with lower effective tax rates (ETRs) for firms that have high internal information quality. The effect of internal information quality on tax avoidance is stronger for firms in which information is likely to play a more important role. For example, firms with greater coordination needs because of a dispersed geographical presence benefit more from high internal information quality. Similarly, firms operating in a more uncertain environment benefit more from the quality of their internal information in helping them to reduce ETRs. In addition, we provide evidence that high internal information quality allows firms to achieve lower ETRs without increasing the risk of their tax strategies (as measured by ETR volatility). Overall, our study contributes to the literature on tax avoidance by providing evidence that the internal information environment of the firm is important for understanding its tax avoidance outcomes.